Informatization and Digitization of Land Relations in Ukraine: Problems and Prospects - Сидор, Вікторія Дмитрівна; Сидор, В. Д.; Сидор, Виктория Дмитриевна; Sydor, Viktoriia D. (Scientific Association for Research and Strategic Studies, 2020)
The relevance of the topic is due to the integration of Ukraine into the world information space. The low level of information society development, e-government and e-democracy, and the digital development of Ukrainian society require immediate steps. The purpose of the paper is to summarize theoretical and normative approaches to the implementation of the process of informatization and digitization of land relations. The study covers the period from 1998 to the present. The author used both theoretical and empirical methods. The creation of the Ministry of Digital Transformation for the first time in the history of Ukraine was a positive innovation. Land management documentation has maintained electronically since 2019. Introduction of electronic land bidding is an important innovation in the field of land relations. Informatization of land relations and reform of the State Land Cadastre will promote transparency of the land market in Ukraine, reduce the cost of planning territories of communities, timely receipt of reliable information about landowners and the value of the land contracts. This will create more favourable conditions for the implementation of land reform and revitalize the investment climate.

Актуальність теми зумовлена ​​інтеграцією України у світовий інформаційний простір. Низький рівень розвитку інформаційного суспільства, електронного уряду та електронної демократії, а також низький рівень цифрового розвитку українського суспільства вимагають негайних кроків. Метою статті є узагальнення теоретичних та нормативних підходів до реалізації процесу інформатизації та оцифрування земельних відносин. Дослідження охоплює період з 1998 року по теперішній час. Використано як теоретичні, так і емпіричні методи. Створення Міністерства цифрової трансформації вперше в історії України стало позитивним нововведенням. Документація із землеустрою ведеться в електронному вигляді з 2019 року. Введення електронних торгів за землю є важливою інновацією у сфері земельних відносин. Інформатизація земельних відносин та реформування Державного земельного кадастру сприятимуть прозорості ринку землі в Україні та своєчасно отримувати надійну інформацію про власників земель та вартість земельних контрактів, зменшать витрати на планування територій громад. Це створить більш сприятливі умови для здійснення земельної реформи та пожвавить інвестиційний клімат.

Актуальность темы обусловлена ​​интеграцией Украины в мировое информационное пространство. Низкий уровень развития информационного общества, электронного правительства и электронной демократии, а также низкий уровень цифрового развития украинского общества требуют немедленных шагов. Целью статьи является обобщение теоретических и нормативных подходов к реализации процесса информатизации и оцифровки земельных отношений. Исследование охватывает период с 1998 года по настоящее время. Использовано как теоретические, так и эмпирические методы. Создание Министерства цифровой трансформации впервые в истории Украины стало положительным нововведением. Документация по землеустройству ведется в электронном виде с 2019 года. Введение электронных торгов за землю является важной инновацией в сфере земельных отношений. Информатизация земельных отношений и реформирование Государственного земельного кадастра будет способствовать прозрачности рынка земли в Украине и своевременно получать надежную информацию о владельцах земель и стоимости земельных контрактов, уменьшать расходы на планирование территорий общин. Это создаст более благоприятные условия для осуществления земельной реформы и оживит инвестиционный климат.
Sydor V. Informatization and Digitization of Land Relations in Ukraine: Problems and Prospects / V. Sydor // Journal of Law & Political Sciences. – V. 23 (2). – Scientific Association for Research and Strategic Studies, 2020. – P. 209-232.
Keywords: digitization; electronic auction; geospatial data; informatization; land relations; state land cadastre; оцифровка; електронний аукціон; геопросторові дані; інформатизація; земельні відносини; державний земельний кадастр; оцифровка; электронный аукцион; геопространственные данные; информатизация; земельные отношения; государственный земельный кадастр; Research Subject Categories::LAW/JURISPRUDENCE